Efecto de la alimentación en la producción de carne de calidad en cuyes. (Cavia Porcellus) - García Ruiz, Félix Humberto (2024)
Guinea pig production in Ecuador has a diverse character, ranging from family to commercial production units, where this practice has been valued for its contribution to food security, as guinea pig meat is appreciated for its protein content and low levels of fat. Therefore, the purpose of this research work is to investigate the nutritional requirements that influence the feeding of guinea pigs(Cavia porcellus) to guarantee meat quality production. Currently, guinea pig production continues to have limitations at an economic and competitive level in the markets; however, producers must adopt strategies that contribute to the adequate management of the feed and the environment to guarantee optimal growth and development. In addition, it is important to ensure overall welfare by minimising stress; it should be noted that new technological trends should cover areas in the feed industry and develop more efficient methods that include alternative, but ecosystem-friendly, ingredients. In addition, it is important to ensure overall well-being by minimising stress; it should be noted that new technological trends must cover areas in the food industry and develop more efficient methods that include alternative, but ecosystem-friendly, ingredients. Due to the growing demand for this species, rural communities have been favoured by the commercialisation of its meat, forming part of the family economy. This has turned them into new opportunities for protein diversification at local and international level; however, this requires the incorporation of essential components that guarantee a higher carcass yield and reduce rearing time.